2011
DOI: 10.1007/s00127-011-0391-7
|View full text |Cite
|
Sign up to set email alerts
|

Family social support, community “social capital” and adolescents’ mental health and educational outcomes: a longitudinal study in England

Abstract: PurposeTo examine the associations between family social support, community “social capital” and mental health and educational outcomes.MethodsThe data come from the Longitudinal Study of Young People in England, a multi-stage stratified nationally representative random sample. Family social support (parental relationships, evening meal with family, parental surveillance) and community social capital (parental involvement at school, sociability, involvement in activities outside the home) were measured at base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
91
1
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(105 citation statements)
references
References 39 publications
8
91
1
5
Order By: Relevance
“…Various studies (Rothon et al, 2012;Smokowski and Bacallao, 2007) and systematic reviews (Bigby, 2012;Jennings et al, 2014) have documented the positive effect of social support in enhancing mental health and well-being of adolescents. Hay and Meldrum (2010) found that a combination of social support and self-control provides adolescents with the ability to deliberate on their stressful life situation and avoid taking actions that might be deleterious to their mental health and well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies (Rothon et al, 2012;Smokowski and Bacallao, 2007) and systematic reviews (Bigby, 2012;Jennings et al, 2014) have documented the positive effect of social support in enhancing mental health and well-being of adolescents. Hay and Meldrum (2010) found that a combination of social support and self-control provides adolescents with the ability to deliberate on their stressful life situation and avoid taking actions that might be deleterious to their mental health and well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the obvious connection between educational aspirations and subsequent education and employment, many youths have no clear aspirations, or they may be indecisive with regard to their aspirations. Educational aspirations are shown to be strengthened by support from family and friends as well as by other psychosocial factors (6)(7)(8), and they are influenced by good mental health and educational skills (7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Mental health has been found to influence educational aspirations and educational attainment in several ways (7,8,10). For example, studies have revealed that externalizing symptoms are related to poorer educational aspirations (9).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, adolescent who has supportive parents score better academically (Rothon, Goodwin, & Stansfeld, 2012).…”
mentioning
confidence: 99%
“…According to Diener (1999), improving quality of life of individual is important for enriching an individual's overall well-being over time including as well as physical and mental health. There are reasons to believe that these assets can affect the health, whether it is school engagement (Bond, et al, 2007), resistance (Parto, 2011), peers (Walsh, et al, 2010), families (Rothon, Goodwin, & Stansfeld, 2012), and neighbourhood (van Voorhees, et al, 2008). In light of these established relationships between developmental assets and youth quality of life, little is known about the relationship between mental health and developmental assets in the context of youth living in suburban community.…”
mentioning
confidence: 99%